Pretherapeutic Assessment of Pancreatic Cancer: Comparison of FDG PET/CT Plus Delayed PET/MR and Contrast-Enhanced CT/MR - Zhang, Zaizhu; Zhou, Nina; Guo, Xiaoyi; Li, Nan; Zhu, Hua; Yang, Zhi (Frontiers in Oncology, 2022)
Purpose This study aims to determine the diagnostic performance of whole-body FDG PET/CT plus delayed abdomen PET/MR imaging in the pretherapeutic assessment of pancreatic cancer in comparison with that of contrast-enhanced (CE)-CT/MR imaging. Materials and Methods Forty patients with pancreatic cancer underwent nonenhanced whole-body FDG PET/CT, delayed abdomen PET/MR imaging, and CE-CT/MR imaging. Two nuclear medicine physicians independently reviewed these images and discussed to reach a consensus, determining tumor resectability according to a 5-point scale, N stage (N0 or N positive), and M stage (M0 or M1). With use of clinical-surgical-pathologic findings as the reference standard, diagnostic performances of the two imaging sets were compared by using the McNemar test. Results The diagnostic performance of FDG PET/CT plus delayed PET/MR imaging was not significantly different from that of CE-CT/MR imaging in the assessment of tumor resectability [area under the receiver operating characteristic curve: 0.927 vs. 0.925 (p = 0.975)], N stage (accuracy: 80% (16 of 20 patients) vs. 55% (11 of 20 patients), p = 0.125), and M stage (accuracy: 100% (40 of 40 patients) vs. 93% (37 of 40 patients), p = 0.250). Moreover, 14 of 40 patients had liver metastases. The number of liver metastases detected by CE-CT/MR imaging, PET/CT, and PET/MR imaging were 33, 18, and 61, respectively. Compared with CE-CT/MR imaging, PET/MR imaging resulted in additional findings of more liver metastases in 9/14 patients, of which 3 patients were upstaged. Compared with PET/CT, PET/MR imaging resulted in additional findings of more liver metastases in 12/14 patients, of which 6 patients were upstaged. Conclusions Although FDG PET/CT plus delayed PET/MR imaging showed a diagnostic performance similar to that of CE-CT/MR imaging in the pretherapeutic assessment of the resectability and staging of pancreatic tumors, it still has potential as the more efficient and reasonable work-up approach for the additional value of metastatic information provided by delayed PET/MR imaging.